2016
DOI: 10.1177/2332858416674007
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Experiment Testing the Efficacy of a Scheduling Nudge in a Massive Open Online Course (MOOC)

Abstract: An increasing number of students are taking classes offered online through open-access platforms; however, the vast majority of students who start these classes do not finish. The incongruence of student intentions and subsequent engagement suggests that self-control is a major contributor to this stark lack of persistence. This study presents the results of a large-scale field experiment (N = 18,043) that examines the effects of a self-directed scheduling nudge designed to promote student persistence in a mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 44 publications
0
32
1
Order By: Relevance
“…Neglecting learner diversity in MOOCs may lead to ineffective or harmful interventions (Deng et al, 2020; Li & Baker, 2018). Baker et al (2016), for instance, found that an intervention designed to promote engagement had a negative effect on completion and performance, particularly for individuals who enrolled in the MOOC shortly before it began and those with ⋅edu email addresses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neglecting learner diversity in MOOCs may lead to ineffective or harmful interventions (Deng et al, 2020; Li & Baker, 2018). Baker et al (2016), for instance, found that an intervention designed to promote engagement had a negative effect on completion and performance, particularly for individuals who enrolled in the MOOC shortly before it began and those with ⋅edu email addresses.…”
Section: Discussionmentioning
confidence: 99%
“…Ferguson et al (2015) found that learners classified as “keen completers” in an eight‐week MOOC fully engaged in most weeks, posted threads in discussion boards and completed assessments on time, while participants labelled as “keen completers” in a three‐week MOOC did not exhibit all these traits in any week. Baker et al (2016) reported that a scheduling nudge designed to promote engagement had weakly significant, moderately negative effects on the number of video lectures watched by MOOC learners. Rogers and Feller (2016) revealed that learners who graded peers' excellent essays in a peer assessment were more likely to quit than those who assessed peers' less exceptional essays.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining the effects of externally and self-imposed interim deadlines on course grades have found positive (e.g., Ariely and Wertenbroch, 2002), negative (e.g., Burger, Charness, and Lynham, 2011), and null effects (e.g., Levy and Ramim, 2013). Studies examining the effects of encouraging students to plan when they will do work have also found a mix of positive (Baker, Evans, Li, and Cung, 2019), negative (Baker, Evans, and Dee, 2016), and null (Sitzmann and Johnson, 2012) effects on course and assignment grades.…”
Section: Introductionmentioning
confidence: 99%
“…7 Our paper also relates to the recent literature on pre-commitment devices in higher education. Himmler et al (2017) find that asking students to pre-commit to taking exams at a certain time improved their overall performance in a graduate business school, while Baker et al (2016) find that prompting students via email to schedule times to watch lecture videos in a Massive Open Online Course had no impact on performance. In a similar setting, Patterson (2015) finds that enabling students to pre-commit to limits on distracting internet time increased completion rates and improved performance but reminding students about their coursework and allowing students to block distractions while working had no significant impact on course outcomes.…”
Section: Introductionmentioning
confidence: 99%